1988
DOI: 10.1051/rnd:19880601
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormones. 1. Polymorphism. (Minireview)

Abstract: Introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 89 publications
0
18
0
Order By: Relevance
“…hGH from Cis International France). All known immunoreactive forms of GH [8][9][10] are recog-nized by this antibody. The lower limit of sensitivity of the assay was 0.5 mIU/1 with intra-and interassay coefficients of variation of 5.3 and 11%.…”
Section: Methodsmentioning
confidence: 99%
“…hGH from Cis International France). All known immunoreactive forms of GH [8][9][10] are recog-nized by this antibody. The lower limit of sensitivity of the assay was 0.5 mIU/1 with intra-and interassay coefficients of variation of 5.3 and 11%.…”
Section: Methodsmentioning
confidence: 99%
“…Duplication of the GH gene was first discovered in primates but further investigation indicated that this event had also occurred in rats, pigs, goats, sheep and cattle (Charrier and Martal, 1988;Wallis et al, 1998). In cattle the two major allelic variants of GH, denoted A (leucine at position 127) and B (valine at position 127), have been identified by Lucy et al, 1993).…”
Section: Basic Physiology Nutritional Factors Influencing Thyroid Fumentioning
confidence: 99%
“…hGH-N gene encodes for the sequence of the major form of hGH, the 22K, as well as the subsequent forms that are derived from it (see &dquo;Growth Hormone. I. Polymorphism&dquo;; Charrier and Martal, 1988) including the 20K variant from an alternative splicing of premessenger RNA (Wallis, 1980;De Noto et al, 1981), and a new natural 17.5K variant (Lecomte et al, 1987 (Frigeri et al, 1979;Kostyo et al, 1985). The second hGH-V gene seems to encode for a polypeptide of 191 amino acids experimentally transcribed in vitro, in which 13 amino acids differ from the 22K of hGH (Pavlakis et al, 1981).…”
Section: Genomic Modifications Hgh Genesmentioning
confidence: 99%
“…The criteria used to define biological activities are based on the well known multiple action of GHs (see &dquo;Growth Hormones. I. Polymorphism&dquo;; Charrier and Martal, 1988, Tables II and III).…”
Section: Introductionmentioning
confidence: 99%